(untitled) (Fiep Bulletin - online, 2011)
The objective of this job is to analyze the theoreticals of Piaget and Vygotsky about how playing in Children Education and Initials Grades of Primary Education. The Job refers about a bibliography research that reveals the importance of the use of playing in two models of Education and its contribution for the development of Child’s psycomotors, cognitives and socials functions. Due to the wide range of games, we also descrive some suggestions and Kinds of games that can be used for de lucid activies. We point also the important roll that the teacher does in the action of playing and in the use of games.After finished the analysis, we can confirm that playing is very important for Child’s social, cognitive, emotional and psycomotor development, as well as is Children Education or Initials Grades of Primary Education. After finished this job, we conclude that the game is a temple of knowledge, where the children that frequent the Children Education and Initials Grades of Primary Education, perform many of their powerfuls trough this resort ludik.